Coronial inquests, indigenous suicide and the colonial narrative - Carpenter, Belinda J. (Critical criminology, 2021)
This article explores the over-representation of Indigenous people in suicide statistics internationally as indicative of the broader impacts of colonialism. The purpose of this discussion in a special issue of critical criminology is to widen the focus beyond criminal justice over-representation and to explore the ways in which research, social policy, and legal institutions align to transform systematically the colonial condition into a medical one. This transformation occurs in three ways. First, a lower evidentiary standard of proof for suicide determination by coroners when the victim is Indigenous is based on a coronial supposition that Indigenous Australians cannot produce a workable response to their disadvantage. Suicide is then interpreted as an understandable response, if not a reasonable one. Second, a focus by suicide researchers on individual risk factors is treated by coroners as an indication of vulnerability to suicide and ignores the collective rates of risk among Indigenous people that cannot equate with the pathological weaknesses of the individual. Third, a paternalistic approach to Indigenous people and communities in social policy positions them as failing subjects of modernity, supposedly requiring a range of government interventions to ensure Indigenous wellbeing. Based on interviews with thirty-two coroners across Australia, as well as an exploration of inquests into clusters of Indigenous suicide in Australia, we argue that differential treatment of Indigenous people in coronial practice is a contemporary feature of the Australian legal, policy, and social landscape, and that the insights are as relevant to criminal justice jurisdictions, as they are to coronial or medico-legal ones.